Accompaniment on Application of Concentrates as Cattle Feed for Palm-Oil Plantation Farmers - Endang Baliarti; Hamdani Maulana; Nono Ngadiyono; I Gede Suparta Budisatria; Panjono Panjono; Tri Satya Mastuti Widi; Muhammad Danang Eko Yulianto; Bayu Andri Atmoko (Jurnal Pengabdian kepada Masyarakat (Indonesian Journal of Community Engagement), 2020)
The activity aims to trial and applies the result of the study of the palm oil plantation-cattle integration system, especially in feed technology, and increase the knowledge and ability of cattle maintenance for Karya Bersama farmers groups. Karya Bersama is one of the farmers’ groups that develop palm oil plantation-cattle integration. The activities are carried out from July to November 2017 at the Sawit-Sapi Center, and the Karya Bersama Farmers Group located in Rokan Hulu District, Riau. The activity began with the socialization of the ingredients, function, benefits of concentrate feed, and concentrate feed production process at Sawit-sapi Center. The activity continued with the application trial of concentrate feed for cattle belonging to farmers and accompaniment for two months. The results showed that the concentrate feed containing 55-60% of palm kernel oil with 17,42% protein content has excellent palatability. Each cattle is given 2 kg/day, always consumed. The activities received a very positive response, so we hope this activity would increase the farmers’ enthusiasm to improve their cow performance.